Performance Analysis and Optimization for Steering Motion Mode Switching of an Agricultural Four-Wheel-Steering Mobile Robot - Jiwei Qu; Hongji Li; Zhe Zhang; Xiaobo Xi; Ruihong Zhang; Kangquan Guo (Agronomy, 2022)
This study focuses on a wheeled mobile robot used for detection, weeding and information monitoring in agriculture. However, it is difficult to reach satisfactory motion mode switching (MMS) performance. This paper aimed at exploring the optimal control parameters guaranteeing smooth MMS of four-wheel steering. Single factor tests were first conducted using a test-bench. A binary quadratic general rotation combination test was designed to obtain the optimal parameters. An entropy weight method was introduced to construct the four indexes as a comprehensive index. The optimal combination of the parameters was obtained, based on the regression equation. The results showed that the two factors and their interaction had a significant impact on the comprehensive index (p < 0.05). The best combinations of the speed of the stepper motor and locking voltage were 56 r·min−1 and 3.96 V for 15° steering, 72 r·min−1 and 4.35 V for 30°, and 107 r·min−1 and 5.50 V for 45°, respectively. A verification test was performed using the prototype of the robot chassis. The results demonstrated that the MMS process was smooth and stable, and the proposed method was effective. This study is a beneficial exploration of the experimental method concerning wheeled robots.